First one is 12^2
second one is 1
5^(x+7)=(1/625)^(2x-13)
We move all terms to the left:
5^(x+7)-((1/625)^(2x-13))=0
Domain of the equation: 625)^(2x-13))!=0
x∈R
We add all the numbers together, and all the variables
5^(x+7)-((+1/625)^(2x-13))=0
We multiply all the terms by the denominator
(5^(x+7))*625)^(2x+1-13))-((=0
We add all the numbers together, and all the variables
(5^(x+7))*625)^(2x-12))-((=0
We add all the numbers together, and all the variables
(5^(x+7))*625)^(2x=0
not sure if this is right :/
Hello :
(2, 6) is a solution of y - x > -3 because : 6-2> -3 ..... 4 > -3
Answer:
<h2>C.</h2>
Step-by-step explanation:
Look at the pictures.
x - sausage
y - bacon
A. 20 pounds of sausage and 90 pound of bacon
x = 20 → y = 100 > 90
B. 40 pound of sausage and 40 pound of bacon
x = 40 → y = 75 > 40
C. 60 pound of sausage and 80 pound of bacon
x = 60 → y = 50 < 80
D. 80 pound of sausage and 20 pound of bacon
x = 80 → y = 25 > 20
Adjacent angles are angles that are side by side (right next to each other). They share a side. #7 and 11 are pairs of adjacent angles.
Vertical angles are angles that are directly across from each other. They are the same angle. #8 and 9 are vertical angles.
#10 and 12 do not fit either of these descriptions so they are neither.